DAMPAK PROGRAM PIJAR TERHADAP UPAYA PENANGGULANGAN KEMISKINAN DAN PENGAANGGURAN DI PROVINSI NUSA TENGGARA BARAT - M Amin (Distribusi - Journal of Management and Business, 2020)
Accelerate the realization of development goals especiallyto reduce poor and unemployment Governur and Vice of Governur of West Nusa Tenggara Province establish priority programe called 'PIJAR (cow, corn, seaweed). This research goals are 1). To know and describe the impact of PIJAR to reduce poor and unemployment in West Nusa Tenggara Prvince. 2). To know and describe the behaviour impact of PIJAR to reduce poor and unemployment in West Nusa Tenggara Prvince. This research data analysis method had been used dynamic system model analysis by powersim 2.5 version software through two steps are arrange causal loop and flow dyagrame. The result of the research showed that PIJAR can reduce poor and unemployment significantly in West Nusa Tenggara Province. b). The behavior of PIJAR impact to reduce poor and unemployment in West Nusa Tenggara.